Temporal Discrimination: Mechanisms and Relevance to Adult-Onset Dystonia - Conte, Antonella; McGovern, Eavan M.; Narasimham, Shruti; Beck, Rebecca; Killian, Owen; O’Riordan, Sean; Reilly, Richard B.; Hutchinson, Michael (Frontiers in Neurology, 2017)
Temporal discrimination is the ability to determine that two sequential sensory stimuli are separated in time. For any individual the temporal discrimination threshold is the minimum interval at which paired sequential stimuli are perceived as being asynchronous; this can be assessed, with high test-retest and inter-rater reliability, using a simple psychophysical test. Temporal discrimination is disordered in a number of basal ganglia diseases including adult onset dystonia, of which the two most common phenotypes are cervical dystonia and blepharospasm. The causes of adult onset focal dystonia are unknown; genetic, epigenetic and environmental factors are relevant. Abnormal temporal discrimination thresholds in adult onset dystonia are associated with structural and neurophysiological changes considered to reflect defective inhibitory interneuronal processing within a network which includes the superior colliculus, basal ganglia and primary somatosensory cortex. It is hypothesised that abnormal temporal discrimination is a mediational endophenotype and, when present in unaffected relatives of patients with adult onset dystonia, indicates non-manifesting gene carriage. Using the mediational endophenotype concept, aetiological factors in adult onset dystonia may be examined including: (i) the role of environmental exposures in disease penetrance and expression; (ii) sexual dimorphism in sex ratios at age of onset; (iii) the pathogenesis of non-motor symptoms of adult onset dystonia; (iv) subcortical mechanisms in disease pathogenesis.